The Use of Tai-Chi to Reduce Anxiety Among Nursing Students Undergoing Simulation. Issue 3 (May 2020) - Mulcahy, Angela; Holland, Brian; Gosselin, Kevin; Pittman, Alison
Abstract : Abstract: This study sought to examine tai-chi as an anxiety-reducing method to increase self-efficacy and improve performance among baccalaureate nursing students experiencing a patient care simulation. The sample included 63 nursing students enrolled in a traditional or second-degree nursing program. The study used a randomized control group pretest-posttest design. Students in the experimental group experienced significant reductions in cognitive and somatic anxiety, along with an increase in self-efficacy and improved performance. Tai-chi can be an effective technique to reduce anxiety and improve self-efficacy and performance among nursing students in simulations.